Metabolic regulation of the Th17/Treg balance in inflammatory bowel disease - Shunfen Zhang; Ruqing Zhong; Shanlong Tang; Liang Chen; Hongfu Zhang (Elsevier, 2024)
Inflammatory bowel disease (IBD) is a long-lasting and inflammatory autoimmune condition affecting the gastrointestinal tract, impacting millions of individuals globally. The balance between T helper 17 (Th17) cells and regulatory T cells (Tregs) is pivotal in the pathogenesis and progression of IBD. This review summarizes the pivotal role of Th17/Treg balance in maintaining intestinal homeostasis, elucidating how its dysregulation contributes to the development and exacerbation of IBD. It comprehensively synthesizes the current understanding of how dietary factors regulate the metabolic pathways influencing Th17 and Treg cell differentiation and function. Additionally, this review presents evidence from the literature on the potential of dietary regimens to regulate the Th17/Treg balance as a strategy for the management of IBD. By exploring the intersection between diet, metabolic regulation, and Th17/Treg balance, the review reveals innovative therapeutic approaches for IBD treatment, offering a promising perspective for future research and clinical practice.